Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1089/dia.2012.0259
|View full text |Cite
|
Sign up to set email alerts
|

Associations ofβ-Cell Function and Insulin Resistance with Youth-Onset Type 2 Diabetes and Prediabetes Among Asian Indians

Abstract: Among Asian Indians, β-cell dysfunction appears to be more strongly associated with T2DM-Y than insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 51 publications
4
35
1
Order By: Relevance
“…Studies have suggested that there could be an accelerated beta cell dysfunction in younger age groups, thus shortening the transition time between prediabetes and T2DM-Y [13,30]. Two recent cross-sectional studies indicate that Asian Indians may be susceptible to early decline in beta cell function even during stages of mild dysglycemia [31,32]. In this context, this study assumes significance as we report decreased betatrophin levels in Asian Indians with T2DM-Y.…”
Section: Discussionsupporting
confidence: 54%
“…Studies have suggested that there could be an accelerated beta cell dysfunction in younger age groups, thus shortening the transition time between prediabetes and T2DM-Y [13,30]. Two recent cross-sectional studies indicate that Asian Indians may be susceptible to early decline in beta cell function even during stages of mild dysglycemia [31,32]. In this context, this study assumes significance as we report decreased betatrophin levels in Asian Indians with T2DM-Y.…”
Section: Discussionsupporting
confidence: 54%
“…Cross-sectional studies indicate that Asian Indians may be susceptible to early decline in b-cell function even during stages of mild dysglycemia (4,5). In this context, this study assumes significance as we report increased SFRP4 levels in Asian Indians even at the stage of IGT.…”
supporting
confidence: 49%
“…The b-cell-related indices were significantly decreased in diabetes converters, while insulin resistance-related parameters did not differ between converters and nonconverters. Several studies have shown that b-cell dysfunction is the major driving factor for the development of overt diabetes in Asians, Pima Indians, and Caucasians [27][28][29][30][31][32]. Differences in underlying b-cell function in each prediabetes category might contribute to the heterogeneous rate of progression to diabetes.…”
Section: Discussionmentioning
confidence: 99%